The interaction of the antitoxin DM43 with a snake venom metalloproteinase analyzed by mass spectrometry and surface plasmon resonance. - Brand, G; Salbo, R; Jørgensen, T; Bloch, C; Boeri Erba, E; Robinson, C; Tanjoni, I; Moura-da-Silva, A; Roepstorff, P; Domont, G; Perales, J; Valente, R; et al. (2012)
DM43 is a circulating dimeric antitoxin isolated from Didelphis aurita, a South American marsupial naturally immune to snake envenomation. This endogenous inhibitor binds non-covalently to jararhagin, the main hemorrhagic metalloproteinase from Bothrops jararaca snake venom, and efficiently neutralizes its toxicity. The aim of this study was to apply mass spectrometry (MS) and surface plasmon resonance (SPR) to improve the molecular characterization of this heterocomplex. The stoichiometry of the interaction was confirmed by nanoelectrospray ionization-quadrupole-time-of-flight MS; from native solution conditions, the complex showed a molecular mass of ~94 kDa, indicating that one molecule of jararhagin (50 kDa) interacts with one monomer of DM43 (43 kDa). Although readily observed in solution, the dimeric structure of the inhibitor was barely preserved in the gas phase. This result suggests that, in contrast to the toxin-antitoxin complex, hydrophobic interactions are the primary driving force for the inhibitor dimerization. For the real-time interaction analysis, the toxin was captured on a sensor chip derivatized with the anti-jararhagin monoclonal antibody MAJar 2. The sensorgrams obtained after successive injections of DM43 in a concentration series were globally fitted to a simple bimolecular interaction, yielding the following kinetic rates for the DM43/jararhagin interaction: k(a) = 3.54 ± 0.03 × 10(4) M(-1) s(-1) and k(d) = 1.16 ± 0.07 × 10(-5) s(-1), resulting in an equilibrium dissociation constant (K(D) ) of 0.33 ± 0.06 nM. Taken together, MS and SPR results show that DM43 binds to its target toxin with high affinity and constitute the first accurate quantitative study on the extent of the interaction between a natural inhibitor and a metalloproteinase toxin, with unequivocal implications for the use of this kind of molecule as template for the rational development of novel antivenom therapies.